Comment on: The interaction of neutrons with 7Be at BBN temperatures: Lack of Standard Nuclear Solution to the "Primordial 7Li Problem" by M. Gai et al. - Schumann Dorothea; Dressler Rugard; Köster Ulli; Paul Michael (EPJ Web of Conferences, 2020)
The recently published article [1] claims to reach quantitative conclusions from a collaborative experiment dedicated to the study of the 7Be(n,α)α reaction. The Authors of this Comment who were collaborators in the experi-ment categorically reject the conclusions therein.